2019
DOI: 10.3390/ijms21010004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Stimulation of Nurr1 Promotes Cell Cycle Progression in Adult Hippocampal Neural Stem Cells

Abstract: Nuclear receptor related-1 (Nurr1) protein performs a crucial role in hippocampal neural stem cell (hNSC) development as well as cognitive functions. We previously demonstrated that the pharmacological stimulation of Nurr1 by amodiaquine (AQ) promotes spatial memory by enhancing adult hippocampal neurogenesis. However, the role of Nurr1 in the cell cycle regulation of the adult hippocampus has not been investigated. This study aimed to examine changes in the cell cycle-related molecules involved in adult hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 115 publications
3
5
0
Order By: Relevance
“…CDKN1B has been reported to regulate G 1 progression and maintain the cell function in response to cell proliferation inhibition or cell differentiation [36,37]. In addition, it has been confirmed that CDKN1B can act as a key modulator in cell growth by induction of CDK2 and Cyclin E1 [38,39]. The findings were consistent to these of previous studies.…”
Section: Plos Onesupporting
confidence: 90%
“…CDKN1B has been reported to regulate G 1 progression and maintain the cell function in response to cell proliferation inhibition or cell differentiation [36,37]. In addition, it has been confirmed that CDKN1B can act as a key modulator in cell growth by induction of CDK2 and Cyclin E1 [38,39]. The findings were consistent to these of previous studies.…”
Section: Plos Onesupporting
confidence: 90%
“…37 Particularly, it is pointed out that the inhibition of the activity of Cyclin-CDK complexes in vitro and the blocking of the cell cycle process by regulating the G 1 to S phase transition are all closely related to p57 KIP2 . 22 Our results showed that there was a notable rise in negative cell cycle regulatory factors, specifically p27 KIP1 and p57 KIP2 , for 24 h after treatment with Mn. More importantly, Nurr1 is considered to be a neuroprotective transcription regulator, which is closely related to the cell cycle.…”
Section: Discussionsupporting
confidence: 48%
“…First, Nurr1 activation by AQ has been linked to neuroprotection. Activation of Nurr1 by AQ leads to the generation of neurons from cortical [ 42 ] and hippocampal [ 42 , 47 , 48 ] neural precursor cells, enhances short-and long-term memory, and improves cognitive deficits in mouse models of Parkinson’s [ 49 , 50 ] and Alzheimer’s disease [ 51 ]. Second, AQ is known to be a selective agonist for Nurr1 with no effect on other members of the NR4A family (Nur77 and NOR1) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%